PENERIMAAN VAKSINASI COVID-19 DI KOTA JAKARTA TIMUR: Analisis Determinan Perilaku - Yehezkiel Gabriel (2022)
COVID-19 is still a pandemic and continues to spread in all countries throughout the world. Vaccination is key measures against the pandemic. DKI Jakarta is one of the provinces that has achieved its vaccination target with 133.2 percent vaccine coverage, but it didn't spread equally throughout the administrative districts of DKI Jakarta. East Jakarta is the area with the lowest vaccine coverage in DKI Jakarta. This study was conducted to analyze the determinants of COVID-19 vaccination acceptance in East Jakarta. Bivariate analysis showed that age, sex, education, knowledge of COVID-19, perception of risk infection, perception of side effects of vaccines, vaccine benefits, attitudes towards vaccines, comorbidities, vaccine access, and access to vaccine information were related to COVID-19 vaccine acceptance. Multivariate analysis showed that the most influential factor on the acceptance of the COVID-19 vaccine was the affordability of the vaccine with POR=19,61. The community is encouraged to learn more about the COVID-19 vaccine, and the government is encouraged to develop vaccination program that is accessible to all groups of people.